Assessment of Prehospital Management of Patients Transported to a Thai University Hospital - Riyapan, Sattha; Chantanakomes, Jirayu; Ruangsomboon, Onlak; Chaisirin, Wansiri; Limsuwat, Chok; Prapruetkit, Nattakarn; Chakorn, Tipa; Monsomboon , Apichaya (Siriraj Medical Journal, 2020)
Objective: To assess the quality of prehospital care given to patients transported to a Thai university hospital. Methods: This prospective observational study collected data from EMS providers who transported patients to Siriraj Hospital during August 2017 to November 2017. Collected data was evaluated by at least 2 EMS medical directors for appropriateness of EMS dispatch and prehospital care. The primary outcome was to determine the quality of prehospital management among patients transported by EMS. Inter-rater variability in the evaluation of patient care between EMS medical directors and medical providers in the emergency department (ED) was performed using Cohen’s kappa coefficient, with a value lower than 0.7 indicating significant variability. Results: Data was collected from 246 EMS providers that transported patients to our center. Evaluation by EMS medical directors found EMS dispatch to be appropriate in 216 cases (87.8%), and patient management to be appropriate in 198 cases (80.5%). Inappropriate prehospital management was found most often in patients who presented with out-of-hospital cardiac arrest (OHCA) (87.5%), and with chest pain (63.6%). Medical providers in the ED rated prehospital management to be appropriate in 93.1% of cases. Cohen’s kappa coefficient between EMS medical directors and ED providers was 0.2, which indicates significant variability between the two groups of assessors. Conclusion: Quality assessment of the Thai EMS system revealed opportunities for improvement in prehospital management of patients dispatched by Thai EMS. Moreover, this study found variability in the evaluation of prehospital care between medical providers at the ED and EMS medical directors. Information from this study will help to influence and guide improvement in prehospital patient care in Thailand.